2008
DOI: 10.1597/07-020.1
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-α and Nonsyndromic Cleft Lip with or without Palate or Cleft Palate Only in Kelantan, Malaysia

Abstract: No evidence of TGFalphaTaq1 polymorphism was observed in association with CL+/-P and CP in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Case-control and case-parent triad studies in humans have reported conflicting results. Although several etiological studies have insisted that NSCLP is associated with allelic variations of TGFA (Ardinger et al, 1989; Shiang et al, 1993; Beaty et al, 2006), others have not observed such an association (Stoll et al, 1992; Lidral et al, 1997; Rahman et al, 2008; Ehlers Bertoja et al, 2008; Zhu et al, 2010).…”
mentioning
confidence: 99%
“…Case-control and case-parent triad studies in humans have reported conflicting results. Although several etiological studies have insisted that NSCLP is associated with allelic variations of TGFA (Ardinger et al, 1989; Shiang et al, 1993; Beaty et al, 2006), others have not observed such an association (Stoll et al, 1992; Lidral et al, 1997; Rahman et al, 2008; Ehlers Bertoja et al, 2008; Zhu et al, 2010).…”
mentioning
confidence: 99%
“…The year of publication ranged from 1989 to 2013, and the sample size ranged from 99 to 921. Among these studies, seven were done in U.S. populations (Ardinger et al, 1989; Hecht et al, 1991, Sassani et al, 1993; Hwang et al, 1995; Shaw et al, 1996; Beaty et al, 1997; Romitti et al, 1999), one in the United Kingdom (Holder et al, 1992), one in Australia (Chenevix-Trench et al, 1992), one in Chile (Jara et al, 1995), one in Japan (Tanabe et al, 2000), one in Denmark (Christensen et al, 1999), two in Brazil (Passos-Bueno et al, 2004; Ehlers Bertoja et al, 2008), one in Malaysia (Rahman et al, 2008), and 11 in China. The genotype distributions among the controls of all included studies were consistent with the Hardy–Weinberg equilibrium ( P >.05).…”
Section: Resultsmentioning
confidence: 99%
“…CLP occurs more commonly in females than males, and clefts involving the lip and palate are the most prevalent (Ali Shah et al, 2015). The aetiology of CLP in Malaysia is multifactorial (Ayu et al, 2003;Rahman et al, 2008;Haque et al, 2015b). The Ministry of Health of Malaysia has conducted various health promotion programmes and initiatives to increase women's awareness of the risk of exposure to environmental factors such as tobacco, alcohol, poor nutrition, medicinal drugs and teratogens, and lack of folic acid during pregnancy.…”
Section: Cleft Care In Malaysiamentioning
confidence: 99%